(untitled) - Rosenberg, Nathan (New York, 1976)
Contents: Some origins of American technology; The generation of new technologies; Diffusion and adaptation of technology; Natural resources, environment and the growth of knowledge
Keywords: Technological innovations,Đổi mới công nghệ; Economic aspects,Khía cạnh kinh tế; United States,Hoa Kỳ